Efeito do acabamento de superfície na estabilidade de cor de resinas para provisório submetidas a desafio corante - Garlet, Katia (2014)
The purpose of this study was to investigate the effect of surface finishing on the color stability of the resins used for provisional restorations when immersed in staining agent in different times (7, 30, and 60 days). Thirty-six disc-shaped specimens (sp) were built up for each type of resin: Duralay (polymethylmethacrylate), Trim II (polyethylmethacrylate) and Protemp 4 (bis-acrylic). The sp were prepared using a muffle with the use of a matrix with dimensions of 10x3 mm. Resins were inserted in the muffle, pressed with 1500 kgf and sp were removed after 15 min. The sp were randomly divided into 2 groups: one was finished with 150-grit sandpaper (rough group) and the other with 150 to 1200-grit sandpapers sequence (polished group). These groups were subdivided into two types of immersion: red wine and saliva (control). Specimens from the wine group were immersed 10 minutes per day and were maintained in saliva along the remained period. Specimens from control group were kept in saliva which was changed every 3 days. The color change (ΔE) was measured with the spectrophotometer SP60 using the CIE L*a*b* system. Data were statistically analyzed by ANOVA and Tukey test (5%). The effect of surface, material and time was statistically significant in red wine (p <0.05). The methylmethacrylate-based resin was superior to the other materials in both storage media, in all periods and in polished and rough surfaces.